Sosialisasi Penelitian Pengembangan (Development Research) bagi Mahasiswa Program Studi Tadris Biologi Universitas Islam Negeri Antasari Banjarmasin - Muhammad Zaini; Amalia Rezeki; Bunda Halang (Universitas Sebelas Maret, 2021)
Community service aims to carry out the dissemination of development research for students of the Biology Tadris Study Program, Antasari State Islamic University, Banjarmasin. The activity was carried out for five months (July-November 2021). Online activities are held once a week for four meetings. The subjects (target audience) were 33 students of the Biology Education Tadris Study Program at IUN Antasari Banjarmasin in the sixth semester of the 2020/2021 academic year, and six biology education lecturers. The implementation method includes three things, namely 1) planning, 2) implementing activities, and 3) evaluation. Community service activities obtained 1) Students of the Biology Tadris Study Program at UIN Antasari Banjarmasin have produced 38 drafts of research proposals for development. One draft proposal that was worked on by a team of lecturers from the Department of Biology became a development research proposal. 2) Students of the Biology Tadris Study Program at UIN Antasari Banjarmasin have been given guidance on scientific publications that become an integral part of the thesis through development research, 3) Students of the Biology Tadris Study Program at UIN Antasari Banjarmasin are given roles and responsibilities to improve teaching materials with ISBN as a supplement to research development.